Effects of zoledronic acid on osteoblasts in three-dimensional culture - Flora Thibaut; Tanguy Watrin; Fleur Meary; Sylvie Tricot; Virginie Legros; Pascal Pellen-Mussi; Dominique Chauvel-Lebret (Elsevier, 2015)
Background/purpose: Bisphosphonates (BPs) are synthetic drugs with antitumor and bone antiresorptive activities. The use of BPs is suspected to favor the emergence of osteonecrosis of the jaw (ONJ), a putative side effect whose pathogenesis remains unclear. Thus, we aimed to get insights about the impact of BPs on osteoblasts functions, using a three-dimensional (3D) culture model, which is suggested to be more similar to the in vivo tissues than monolayers. Materials and methods: Effects of low (0.1 μM) and high (10 μM) concentrations of zoledronic acid were investigated on osteoblasts (hFOB 1.19), cultured as multicellular spheroids (MCS). Proliferation, apoptosis, spheroid growth kinetics, and morphology were studied using the 3-(4,5-dimethyl-thiazoyl-2yl) 2,5-diphenyl-tetrazolium bromide (MTT) and acid phosphatase (APH) assays, caspase 3 Western-blotting, phase contrast imaging and scanning electron microscopy (SEM). Results: Proliferation, apoptosis, and spheroid morphology showed that 10 μM zoledronic acid (ZA) induced a significant reduction in the relative viable cell number, correlated with morphological alterations of spheroids, and induction of apoptosis. A lower ZA concentration (0.1 μM) promoted cell proliferation without affecting growth kinetics or spheroid morphology. Conclusion: ZA sensitivity of osteoblasts depends on concentration and experimental models. The dual dose-dependent effects of ZA on osteoblasts cultured as spheroids, thereby promoting or inhibiting cell proliferation, may provide opportunities in tissue engineering. At last, the hFOB spheroid culture system represents a valuable model for the exploration of the molecular basis of BPs action on osteoblasts and for the development and evaluation of implantable biomaterials in bone sites.